The 1, 8-naphthyridines sulfonamides are NorA efflux pump inhibitors. (March 2021) - Oliveira-Tintino, Cícera Datiane de Morais; Muniz, Débora Feitosa; Barbosa, Cristina Rodrigues dos Santos; Pereira, Raimundo Luiz Silva; Begnini, Iêda Maria; Rebelo, Ricardo Andrade; Silva, Luiz Everson da; Mireski, Sandro Lucio; Nasato, Michele Caroline; Krautler, Maria Isabel Lacowicz; Pereira, Pedro Silvino; Costa, José Galberto Martins da; et al.
Highlights: 1, 8-naphthyridine sulfonamides showed synergy with norfloxacin and ethidium bromide. MICs of multidrug-resistant S. aureus strains SA-1199 and SA-1199B were reduced. In silico tests agreed with microbiologic results, with clinically relevant values. Compounds had favourable interaction energy and undergo gastrointestinal absorption. Data suggest that the drug would be relatively non-toxic for individual consumption. 1, 8-naphthyridines possibly inhibit the NorA efflux pump. Abstract: Objective: Efflux pumps are transmembrane proteins associated with bacterial resistance mechanisms. Bacteria use these proteins to actively transport antibiotics to the extracellular medium, preventing the pharmacological action of these drugs. This study aimed to evaluate in vitro the antibacterial activity of 1, 8-naphthyridines sulfonamides, as well as their ability to inhibit efflux systems of Staphylococcus aureus strains expressing different levels of the NorA efflux pump. Methods: The broth microdilution test was performed to assess antibacterial activity. Efflux pump inhibition was evaluated in silico by molecular docking and in vitro by fluorometric tests, and the minimum inhibitory concentration (MIC) was determined. The MIC was determined in the association between 1, 8-naphthyridine and norfloxacin or ethidium bromide. Results: The 1, 8-naphthyridines did not show direct antibacterial activity. However, they effectively reduced the MIC of multidrug-resistant bacteria by associating with norfloxacin and ethidium bromide, in addition to increasing the fluorescence emission. In silico analysis addressing the binding between NorA and 1, 8-naphthyridines suggests that hydrogen bonds and hydrophilic interactions represent the interactions with the most favourable binding energy, corroborating the experimental data. Conclusion: Our data suggest that 1, 8-naphthyridines sulfonamides inhibit bacterial resistance through molecular mechanisms associated with inhibition of the NorA efflux pump in S. aureus strains.